Transvisível: (in)visibility of the LGBTI+ population in artistic creation and its pedagogical approach (Revista Apotheke, 2021)
This article discusses gender differences based on the experience of artistic exhibitions in educational spaces, through the insertion of Transvisible work as a pedagogical tool for promoting the debate on sexuality and gender. In the first part, we will address data and references from the research project that gave rise to the creation of the Transvisible work, in its relations with forms of dress, expression and with the (in)visibility of the LGBTI + population. Then, the experiences of exposure in formal and non-formal educational spaces will be presented, articulating the reports of the experiences and perceptions raised. Finally, we consider the importance of the experience of exhibiting the work in these educational spaces, the potentialization of discussions on gender differences and the violence suffered by the LGBTI + population, as well as on the importance of the university-community-school articulation, which structured the experience of this work, from its conception to its enjoyment.
Keywords: art; education; genre; school; LGBTI